What drives startup valuations? - Imbierowicz, Björn; Rauch, Christian (Journal of Banking & Finance, 2024)
We find that valuations of Venture Capital-backed startup companies invested by mutual funds are driven by their peer valuations rather than their fundamentals, such as operating performances. As startups oftentimes experience substantial valuation changes at their Initial Public Offerings (IPO), we also investigate the share pricing transition of startups from private to public companies. We find that more active pricing of shares prior to the IPO correlates with smaller discrepancies between private and public valuations as well as lower IPO mispricing, suggesting a link between private and public market pricing efficiency. Jointly, our results help investors and regulators achieve a better understanding of the dynamics behind misvaluation in private assets in general, and startups in particular.